Nucleation bursts of primary intermetallic crystals in a liquid Al alloy studied using in situ synchrotron X-ray radiography - Feng, S; Liotti, E; Lui, A; Wilson, MD; Grant, PS (Elsevier, 2021)
The nucleation of primary Pt-rich intermetallic compound (IMC) crystals was studied in a model Al-Pt-Er alloy as an analogue to AlFe that forms in commercial Al alloys. The Pt-rich IMCs provided strong X-ray absorption contrast that allowed earlier detection of formation events and the resolution of solute diffusion fields. Crystal formation behaviour was investigated during directional and isothermal solidification when the alloy was inoculated with TiB particles at cooling rates of 0.1 Ks to 8 Ks using in situ synchrotron X-ray radiography. Different from previous studies that concerned disordered, solid solution phases such as -Al dendrites, for the first time nucleation bursts of ordered compound crystals were observed, where the nucleation of the IMC crystals proceeded in distinct cascades (in the time domain) or waves (in the spatial domain), the magnitude of which increased with increasing cooling rate and particularly with decreasing thermal gradient in the melt. Comparing the crystal number density with the estimated number density of TiB particles suggested that the IMC crystals nucleated only on the most potent TiB particles, accounting for 0.5% of the total TiB number density in the melt. The effect of the thermal gradient and cooling rate on the magnitude of the nucleation waves and the IMC number density was revealed in terms of the available undercooling in the liquid in front of an individual IMC and the solute depleted liquid fraction that arose from the interaction of an ensemble of IMC crystals.